Best Practices for Sustainable Development of Micro Hydro Power in Developing Countries - Khennas, Smail (World Bank, Washington, DC, 2014)
This report synthesizes the experience of micro hydro developments in Sri Lanka, Peru, Nepal, Zimbabwe, and Mozambique. It attempts to draw out the Best Practice from this experience. Micro hydro plants are defined as having a capacity of between 10 kW and 200 kW. The report provides a rigorous comparative microeconomic analysis of the cost and financial returns of a sample of plants across the five countries. It draws out the macroeconomic, financial, and other institutional arrangements that appear important to the scaling-up of micro hydro investments. Summaries of the microeconomic analysis of the case studies of individual micro hyro plants are included in the annex to this synthesis report. The lessons for "Best Practice" are summarized in Section 5.